A comparative study of ultrasound and infrared transesteri?cation of Sterculia foetida oil for biodiesel production - Kusumo F.; Silitonga A.S.; Ong H.C.; Masjuki H.H.; Mahlia T.M.I. (Taylor and Francis Inc., 2023)
Alternative fuels; Biodiesel; Energy utilization; Infrared radiation; Mass transfer; Transesterification; Ultrasonics; Acid value; Biodiesel production; Comparative studies; Infrared technique; KOH Catalysts; Sterculia foetida; Ultrasound techniques; Ultrasonic applications